Effect of the TLR2/MyD88/NF-κB axis on corneal allograft rejection after penetrating keratoplasty. (2nd January 2016) - Wu, Wei; Yu, Shengyou; Feng, Songfu; Yang, Jize; Lu, Xiaohe
Abstract: Purpose : To evaluate the effect of the TLR2 (Toll-like receptor 2)/MyD88/NF-κB axis on the allograft rejection after penetrating keratoplasty (PK). Methods : The PK rat models were randomly divided into four groups: allograft group, dexamethasone group, PDTC group and isograft group. The mean survival time (MST) and rejection index of corneal grafts were observed. The immunohistochemical staining of TGF-α was performed on day 15. The messenger RNA (mRNA) and protein expression of TLR2, MyD88 and NF-κB p65 in corneal grafts were detected by reverse transcription–polymerase chain reaction (RT–PCR) and western blotting. Results : On days 5, 7, 9, 11, 13 and 15, the rejection index in the allograft group was higher than in the other three groups ( p < 0.05). The MST in the PDTC group (MST, 23.30 ± 0.42 days, n = 10) and in the dexamethasone group (MST, 24.40 ± 0.50 days, n = 10) were higher than in the allograft group (MST, 14.7 ± 0.70 days, n = 10) ( χ 2 = 18.02, p < 0.01; χ 2 = 21.47, p < 0.01). The expression of TNF-α in the PDTC group and in the dexamethasone group decreased compared with the allograft group by immunohistochemistry. On day 15, the mRNA and protein expression of TLR2, MyD88 and NF-κB p65 in the PDTC group and the dexamethasone group were less than in the allograft group ( p < 0.05). Conclusions : Expression of TLR2, MyD88 and NF-κB p65 in rat corneal graft increased significantly and concurred with the allograft rejection, but were effectively inhibited by the treatment with dexamethasone and PDTC after PK. Dexamethasone could improve corneal allograft survival by the TLR2/MyD88/NF-κB axis. PDTC could suppress corneal graft rejection by inhibiting the activity of NF-κB. The TLR2/MyD88/NF-κB axis maybe a potential therapeutic target for corneal allograft rejection.